A novel internal fixation technique for chronic elbow dislocations: Technical note and case report - Amir Bisadi; Fatemeh Abbasi; Mohammad Abbasalizadeh; Morteza Gholipour (Radiology Case Reports)
Neglected elbow dislocations are difficult to treat and often lead to functional impairment, especially in resource-limited settings with limited surgical options. We report a case of a 40-year-old male who presented with a neglected elbow dislocation 8 weeks postinjury. Upon presentation, he exhibited a severely restricted range of motion and pain. The surgical approach involved the use of a modified T-plate adapted for resource-limited settings. Postoperatively, the elbow's range of motion was significantly enhanced, and stability was restored, demonstrating the efficacy of the adapted techniques.